Effect of Collagen Cross-linking on Rigid Gas Permeable Contact Lens Comfort in Keratoconus - Sharafat Javaheri; Mahmood Nejabat; Asieh Ehsaei; sahar mohaghegh; Zahra Tajbakhsh (Journal of Ophthalmic & Vision Research)
Purpose: To compare rigid gas permeable (RGP) contact lens comfort in patients with keratoconus who underwent corneal cross-linking (CXL) versus those without CXL surgery. Methods: This prospective study was carried out on 41 eyes (25 patients). Specifically, 21 eyes were assigned to the CXL group and 20 eyes to the non-CXL group. All of the patients were fitted with RGP lenses. The patients were also assessed one and three months after the initial RGP fitting. They were asked to grade themselves on a scale from 1 to 4 according to the frequency and intensity of ocular discomfort, vision fluctuation, and overall comfort with RGP lenses. Results: The mean age of participants was 24.5 ± 3.20 years. There was no significant difference in the intensity of fluctuations in vision (P = 0.30), frequency of discomfort (P = 0.29), and intensity of discomfort (P = 0.31) between the two groups during the one- and three-month follow-up interviews. Conclusion: Based on the current study, there is no significant disparity in self-reported discomfort with RGP contact lenses between patients with keratoconus who have undergone corneal CXL and those who have not.